INVENTARISASI POTENSI PAKAN KUSKUS DI TAMAN NASIONAL MANUSELA (RESORT MASIHULAN) - Kunu, Pretty; Puttileihalat , Maya; Sahusilawane, John (PT. BARRINGTONIA ASIATICA LESTARI, 2024)
This research aims to determine the types of plants that have the potential to be used as cuscus food, determine the parts of plants that function as cuscus food, and determine the availability of cuscus food in their habitat. This research uses a descriptive method using the route transect technique carried out in Manusela National Park (Masihulan Resort). The research instrument generally carried out by researchers is field observation. The data obtained consisted of the type of feed consumed by cuscus, the plants consumed by cuscus (leaves, fruit and bark), and the potential types of feed (density, dominance and frequency) at the research location. The results of data analysis show that there are 27 types of plants that are categorized as cuscus food in the research area and the most preferred cuscus are Bintanggur (Calophyllum inopyllum), Wako (Carallia brachiate merr.), Wapane, Forest Nutmeg (Knema cinerea), Redwood (Pinus sylvestris), Forest Belo (Diospyrus celebica), Siki Wood (Palaquium javense burck). The results of the research show that the part of the plant most liked and consumed by cuscus is the leaves of young shoots in very large quantities compared to the fruit and bark of the tree. Finally, the research results show that the availability and regeneration of cuscus feed is still very good, this can be seen from the dominance values ​​obtained both at tree level and at pole level.